Exploring Talent Retention Strategy in a Financial Technology Company - Mohd Rafiq, Mohamad Mazlan (2020)
The purpose of this study was to focus on talent retention strategy, through the practices in talent management. This was done by investigating the reasons of high talent turnover, identifying the solutions and the best practices in retaining and managing the talents, specifically in a financial technology company in Malaysia. There were seven experienced talented employees of the company participated in the semi-structured interviews. The data from the interviews were critically analyzed and the findings were successfully identified. The findings indicated that there are five reasons that lead to talent retention at the company namely work environment, leadership style, compensation and benefits, career advancement, flexible working hours and work experience. As for the six reasons most of the talents left the company, these include better career opportunity, unclear company’s direction, and superior subordinate relationship, lack of recognition and appreciation, nature of business and better monetary rewards. The findings also revealed six solutions for the current talents to stay which are, leadership style, quality management, career development, compensation and benefits, information sharing and appreciation and recognition. As for the best practices in managing the talents, the findings identified seven best practices which include career development, compensation and benefits, hiring process, workplace flexibility, feedback session, employee engagement and organizational strategy.